Modulation and control strategies for neutral-point-clamped converters - Beniwal, Neha (Nanyang Technological University, 2021)
This thesis presents modulation and control strategies for neutral-point-clamped (NPC) converters. These converters produce ac voltages with lower harmonic distortion and the switches operate with less switching frequencies than traditional two-level voltage-source converters. NPC converters are widely employed in grid integration of renewable energy sources like solar and wind energy, high-power motor drives, shunt active power filters, etc. The NPC converters suffer from challenges such as, the subsequent increase in switching losses while controlling the capacitor voltage (CV) ripples, neutral-point (NP) voltage instability arising in the presence of nonlinear loads enriched in even-order harmonics, and the divergence of CVs in the presence of nonzero average NP current. The focus of this thesis is to address these challenges and develop more efficient modulation and control techniques for the NPC converters. In order to find a trade-off solution between the CV ripple magnitude and the switching power losses, a new feedforward compensated modulation technique for the three-phase NPC converter is proposed in this thesis. With this technique, the CVs are limited within a predefined voltage band. An innovative feedforward compensation is introduced to avoid low-frequency distortion on the output voltages of the converter arising due to oscillations in the CVs. Limiting the CV ripples helps in the design of the NPC converter, since the maximum voltage that the dc-link capacitors and the power semiconductors have to withstand is predefined. Though the proposed feedforward compensated modulation strategy offers a trade-off between the CV ripples and switching losses, its performance deteriorates in the presence of extreme nonlinear loads due to the tendency of the CVs to frequently bounce out of the voltage band leading to higher switching losses. In order to address this drawback, a band-limited three-level (BL-3L) modulation technique is proposed which aims to balance the average CVs without any substantial increase in the switching losses, thereby concentrating mainly on enhancing the steady state performance of the system. In addition to the predefined voltage band (applied to the CVs), a variable current band is applied to the phase currents. The size of the current band is varied based on the tendency of the operational condition to unbalance the NP. Therefore, the BL-3L modulation is another approach to have a trade-off between the CV ripples and the switching power losses, which ensures the average CVs are balanced even in the presence of nonlinear loads enriched in even-order harmonics. For bipolar dc-bus applications of NPC converters like feeding multiterminal dc-loads, back-to-back systems and grid-connected photovoltaic (PV) systems, the main challenge is to generate the required nonzero average NP current which, if not compensated, causes the CVs to diverge and hence destabilizes the converter. In order to address this issue, a dual-mode modulation technique is proposed which utilizes the inherent capability of the NPC converter to generate the required average NP current and does not employ any additional hardware. This technique is developed analytically using ac-side voltages and currents, and is applicable for all bipolar dc-bus applications of the NPC converter with balanced CVs. The analytical solution also provides the maximum average NP current injection capacity of the NPC converter, which defines the stable operating region of the converter. The applications of dual-mode modulation technique are limited to systems with balanced CVs. In order to extend this analysis to applications of the NPC converter with unbalanced CVs, a dual-input NPC inverter-based grid-connected PV system is considered. A control strategy is proposed for this system to asymmetrically control the PV arrays without incorporating any additional external circuit. This is achieved by employing an analytically developed linearization block, similar to the dual-mode modulation technique, which helps in generating the required NP current to counter for the difference in the PV currents. Experimental results are obtained on a laboratory developed prototype to validate all the proposed modulation techniques under different operating conditions. Finally, this thesis summarizes the work that has been done and presents some directions for future research.